Hot topic: new research highlights the need for holistic thinking about transition cows - Bradford, Barry J. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2014)
In the past, efforts to improve the transition to lactation have focused largely on preventing infections and maximizing energy intake in transition cows, and these issues have generally been treated independently. New models, however, are emerging to explain the development of numerous transition disorders. A combination of insults, including social stress, negative energy balance, heat stress, endotoxin exposure, and oxidative stress may promote inflammation, suppress feed intake, and impair both metabolic and immune function during the transition period. These models suggest that transition cow management must be viewed holistically, because the cow’s environment, nutrition, and immune function interact in many complex ways. Fortunately, a number of practical approaches can be used to improve the overall health of transition cows, which can decrease the cull rate in early lactation and improve both productivity and reproductive success.
Dairy Research, 2012 is known as Dairy Day, 2012
Keywords: Dairy cattle; Lactation; Health; Productivity; Reproduction